Solving an industrially relevant quantum chemistry problem on quantum hardware - Nützel, Ludwig; Gresch, Alexander; Hehn, Lukas; Marti, Lucas; Freund, Robert; Steiner, Alex; Marciniak, Christian D.; Eckstein, Timo; Stockinger, Nina; Wolf, Stefan; Monz, Thomas; Kühn, Michael; et al. (Quantum Science and Technology, 2025)
Quantum chemical calculations are among the most promising applications for quantum computing. Implementations of dedicated quantum algorithms on available quantum hardware were so far, however, mostly limited to comparatively simple systems without strong correlations. As such, they can also be addressed by classically efficient single-reference methods. Here we calculate the lowest energy eigenvalue of active space Hamiltonians of industrially relevant and strongly correlated metal chelates on trapped ion quantum hardware, and integrate the results into a typical industrial quantum chemical workflow to arrive at chemically meaningful properties. We are able to achieve chemical accuracy by training a variational quantum algorithm on quantum hardware, followed by a classical diagonalization in the subspace of states measured as outputs of the quantum circuit. This approach is particularly measurement-efficient, requiring 600 single-shot measurements per cost function evaluation on a ten qubit system, and allows for efficient post-processing to handle erroneous runs.
CRIS-Team Scopus Importer:2025-01-31
Keywords: quantum algorithms for chemical calculations; quantum chemistry; quantum computing; trapped ions